Phytochemical Screening and Antioxidant Activity of Mimosa tenuiflora (Willd.) Poir Root Extracts - Barajas-Carrillo, Victor Wagner; Covantes-Rosales, Carlos Eduardo; Castrejón-Medina, Valeria Estefanía; Mendoza-Martínez, Alexander Manuel; Toledo, Saul; Bueno-Durán, Adela Yolanda; Zambrano-Soria, Mercedes; Díaz-Resendiz, Karina Janice Guadalupe; Díaz-Rubio, Laura Janeth; Córdova-Guerrero, Iván (Sciences of Phytochemistry, 2026)
This study evaluated the phytochemical profile and antioxidant activity of extracts and partitions derived from the root of Mimosa tenuiflora (Willd.) Poir., also known as tepezcohuite. Three extracts were prepared through hydroalcoholic maceration, total alkaloid extraction, and Soxhlet extraction. Additionally, four partitions were obtained from the ethanolic extract using the modified Kupchan technique: n-hexane, dichloromethane, n-butanol, and water. Qualitative phytochemical screening showed the presence of alkaloids, tannins, flavonoids, saponins, steroids, triterpenoids, reducing sugars, coumarins, and cardiac glycosides in various several fractions, while no anthraquinone glycosides were detected. Antioxidant activity was assessed using DPPH and ABTS assays. In the DPPH assay, the most active fractions were the butanolic (EC50 = 2.20 ± 0.45 µg/mL) and the ethanolic (EC50 = 2.25 ± 0.01 µg/mL). While, in the ABTS assay, the ethanolic extract and butanol partition were the most active fractions with EC50 values of 4.87 ± 1.11 µg/mL and 5.43 ± 0.21 µg/mL respectively. The less polar fractions (n-hexane, Soxhlet) exhibited lower activity. This study expands the phytochemical knowledge of M. tenuiflora, focusing on its roots, an organ less extensively characterized than the bark regarding its comprehensive phytochemical and antioxidant profile. The results show that this organ is a promising source of bioactive metabolites with antioxidant capacity. This finding justifies further investigation into the pharmacological and therapeutic applications of these compounds, which is particularly relevant given that while previous research has systematically favored the bark, and existing root studies have focused primarily on specific alkaloids, comprehensive profiling remains limited.